Business Education for Corporate Social Responsibility and Social Justice - Shannon Deer; Jill Zarestky (Adult Education Research Conference, 2016)
Social justice and corporate social responsibility are concepts business schools struggle to incorporate into curriculum at the undergraduate and graduate levels. Using qualitative methods, this study explored the impact adult education principles and practices had on business students’ beliefs, assumptions, and values towards social justice and corporate social responsibility.
Keywords: social justice; adult education; business